2020
DOI: 10.1111/pin.13007
|View full text |Cite
|
Sign up to set email alerts
|

A case of Langerhans cell sarcoma on the scalp: Whole‐exome sequencing reveals a role of ultraviolet in the pathogenesis

Abstract: Langerhans cell sarcoma (LCS) is a high‐grade neoplasm with overtly malignant cytological features and a Langerhans cell phenotype. The underlying genetic features are poorly understood, and only a few alterations, such as those of the MARK pathway‐related genes, CDKN2A and TP53 have been reported. Here we present a 70‐year‐old male with LCS on the scalp and pulmonary metastasis. The multinodular tumor, 3.0 cm in diameter, consisted of diffusely proliferated pleomorphic cells with numerous mitoses (53/10 HPFs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…This finding was also further supported within the case report published by Kim et al, which also discussed on the presence of TP53 mutations in LCS as well as presenting us with a whole exonome analysis of LCS [12]. A further report published by Katsuragawa et al, also discussed about TP53 mutations and its presence within LCS; this report also discussed about CDKN2A deletion, which has rarely been seen within LCS [53]. This was a unique study because for the first time it discussed that the accumulation of damaged DNA by ultraviolet light could be a pre-disposing factor for the development of LCS.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This finding was also further supported within the case report published by Kim et al, which also discussed on the presence of TP53 mutations in LCS as well as presenting us with a whole exonome analysis of LCS [12]. A further report published by Katsuragawa et al, also discussed about TP53 mutations and its presence within LCS; this report also discussed about CDKN2A deletion, which has rarely been seen within LCS [53]. This was a unique study because for the first time it discussed that the accumulation of damaged DNA by ultraviolet light could be a pre-disposing factor for the development of LCS.…”
Section: Discussionsupporting
confidence: 75%
“…This was a unique study because for the first time it discussed that the accumulation of damaged DNA by ultraviolet light could be a pre-disposing factor for the development of LCS. This study also further gave evidence that due to the overload of mutational burden and possible increased PD-1 expression within tumor cells therapy by immune-checkpoint inhibitors may provide benefit for the treatment of unresectable LCS [53]. Another intriguing study also supported the previously discussed theory of LCS arising from other hematopoietic tumors, however, this study also presented us with a new finding of the detection of KRAS p.G13D mutations on flourescence in situ hybridization analysis of LCS arising from follicular lymphoma.…”
Section: Discussionmentioning
confidence: 65%
“…[1][2][3] Diagnosis of primary Langerhans cell sarcoma is difficult, and it is necessary to differentiate it from other malignancies of the skin, including anaplastic large cell lymphoma, 4 malignant melanoma, 5 metastatic cancer, myeloid sarcoma, and malignant fibrous histiocytoma. 6 Langerhans cell sarcoma occurs at any age and involves many organs or tissues, including bone marrow, 7 lung, 8 lymph nodes, 9 liver, 10 skin, [11][12][13] and subcutaneous tissue. 14 Our case indicated that the differential diagnosis of Langerhans cell sarcoma should be borne in mind for cases with high FDG uptake of skin mass.…”
Section: Figurementioning
confidence: 99%